Hormonal influence on adventitious or callus mediated regeneration from zygotic embryos in Jatropha curcas - KUMARI, MAYA; PATADE, VIKAS Y; ARIF, MOHOMMAD; AHMED, ZAKWAN (The Indian Journal of Agricultural Sciences, 2013)
Jatropha curcas L. is being perceived as potential biofuel crop with the growing petroleum prices and depleting oilresources. Limited research has been carried out for genetic improvement in this crop. For gene enrichment throughgenetic manipulation an efficient, high frequency and reproducible in vitro regeneration protocol from any explant type is a prerequisite. In view of this, the present study was conducted to optimize in vitro regeneration from zygotic embryos of Jatropha curcas. Adventitious regeneration was obtained directly from zygotic embryos in Murashige and Skoog (MS) medium supplemented with 2 mg/l 6-benzylamino purine (BAP) (>14 shoot buds) and in 4 mg/l BAP (12 shoot buds)without addition of any other hormone. Cytokinin (BAP) combined with auxins (IAA-Indole-3-acetic acid, IBA-Indole3-butyric acid, NAA-Naphthalene acetic acid) gave rise to callus, which continued to proliferate with maximum of 7shoots, when transferred in regeneration media (MS + 2 mg/l BAP + 1 mg/l GA3). This indicates the influence of hormoneson the direct and indirect regeneration from the same explant. Mother explant continued to produce shoots upon successivesubculturing. The highest frequency of root induction (80%) was observed on half MS medium with 0.5 mg/l IBA.Regenerated plantlets were hardened under culture room growth conditions. The present regeneration protocol may proveto be promising for genetic improvement through genetic transformation and induction of somaclonal variations throughin vitro mutagenesis.